Usulan Perbaikan Proses Produksi Pada CV. Kandayas Furniture dengan Pendekatan Model Simulasi Sistem - Tarmizi, Akmal; Yandeza, Gilang; Nurkhaerani, Fatma; Wahyudin, Wahyudin (Fakultas Teknik Universitas Tulang Bawang, 2024)
Kandayas Furniture is one of the companies engaged in manufacturing tables. The table production process goes through several stages. Based on field observations and interviews that have been conducted, problems arise from the company's production process. The problem exists in the assembly process because many products are waiting, so there is a buildup in the assembly process of the table. The buildup occurs because the assembly process to the finished material warehouse has a considerable distance difference. This resulted in an ineffective production process. Then, in Promodel Now the movement of each work station still uses human labor which results in delays in the production process. From this problem, it is obtained that the process flow changes are more structured, the material handling distance from assembly to finished goods is shorter because there are changes in the lay out that we propose and make material handling time more efficient, using handlift conveyance in each flow, adding assembly operators due to bottlenecks in assembly due to the paint drying process, using a paint oven machine for drying paint to shorten the time and reduce the accumulation of goods, and implementing K3 according to the SOP so that employees avoid work accidents. Keywords: Bottleneck; Productivity; ProModel Software; System Simulation